PARTISIPASI MASYARAKAT DALAM PEMULIHAN PARIWISATA PADA ERA NEW NORMAL DI KSPN BEDUGUL - Nyoman Reni Ariasri; Hartanti Woro Susianti (JURNAL KEPARIWISATAAN, 2022)
The research aims to investigate community participation in KSPN Bedugul towards tourism recovery efforts. Data was collected by observation, survey and interview using questionnaires and interview guides. The sampling technique used was purposive and snow ball sampling and the data obtained were analyzed using quantitative descriptive analysis techniques and the typology theory of community participation in tourism from Pretty were referred to. The results showed that the overall community participation in the recovery of tourism in the New Normal era at KSPN Bedugul, appears very small (below 50%). Based on the seven levels of participation typology, the level of participation in the Bedugul community from the lowest can be seen as follows: manipulative participation with average value of 0.556 or 27.8%; passive participation (0.546 or 27.3%); participation by consultation (0.563 or 28.1%); participation for material incentives (0.82 or 41%); functional participation (0.293 or 14.6%); interactive participation (0.156 or 7.8%); self-mobilization and connectedness (0.9 or 45%). It is recommended that stakeholders involve the community in tourism recovery efforts, as well as the re-establishment of organizations such as Pokdarwis. It is also necessary to increase public awareness of the meaning of tourism for improving their standard of living.